Legal protection of children as victims of associal crimin1wal at the binjai police (police report study lp/b/447/iv/2022/spkt) - Johannes Pangeran LS; Eka Kristinna Baene; Yusuf Hanafi Pasaribu (LEGAL BRIEF, 2023)
Immoral acts against children are crimes that violate morals, morality and religion. The impact of this crime on children is to cause physical and psychological trauma to victims, especially children, so that it can affect the victim's self-development when he grows up. The problem in this research is how is the legal protection for child victims of immoral crimes based on Law Number 35 of 2014 concerning Child Protection. The type of research used in this study is a normative method. Data collection is done by literature study and field study. Data were analyzed qualitatively to obtain research conclusions. The results of the research and discussion show that legal protection for child victims of immoral crimes based on the legal protection of children in Law Number 35 of 2014 fulfills the legal interests of children as victims of criminal acts because it refers to comprehensive protection for child victims of immorality and fulfills children's rights in the enforcement process law and provide rehabilitation to children, either medically or psychologically. The form of legal protection for children as victims of immorality is carried out in an integrated and continuous manner starting from the level of the police, prosecutors and courts. Legal protection for child victims of immoral crimes based on the Child Protection Act shows that the enactment of this law provides comprehensive protection. For this reason, it is suggested that law enforcement officials are advised to be more intense in dealing with legal protection issues for children and should further increase socialization in order to disseminate knowledge and awareness to the community, especially people who are in remote, rural areas, with low educational and economic backgrounds. , about the importance of legal protection for children.